A STUDY OF THE SOCIAL AND PERSONAL ADJUSTMENT OF MALE AND FEMALE PHYSICAL EDUCATION TEACHERS IN THE PREPARATORY STAGE IN BASRA GOVERNORATE (ResearchJet Journal of Analysis and Inventions, 2022)
Study the social and personal compatibility of the teachers and teachers of physical education in the preparatory stage of Basra Governorate